IS THE BOOK BY VECIHI TIMUROĞLU “FAIRYTALE FOR FIRA”T REALLY A FAIRYTALE BOOK? - Munise AKSÖZ (Fırat University, 2020)
There are 11 tales in Vecihi Timuroğlu's book “Tales for Fırat” contains 11 tales. Timuroğlu have compiled 10 of these tales by traveling the Turkey region-by-region, which later he redacted in his own style and published as a book. 10 of these tales in this book has been compiled from Turkey's Hakkâri (Turaç Kız), Silifke (The Legend of Maiden's Castle), Diyarbakır (Amidih Piri), Rize (Avcı Pirim), Tarsus (Kahf Eshabı), Başkale (Caves of Mount Ararat), Mt. Suphan (Legend of Mount Ararat), Kars (Uğuz) and Sivas (City of the poets) regions; while one is excerpt from the book “Jami’ al-Tawarikh” (Ergenekon) by the Mongol historian Rashid-al-Din. In the book is only the region of the story "the birth of Fırat" not specified. But many place names that can be found on the map are given. A structure that distinguishes these tales stands out in the book. Even though these narratives are generally classified as tales, they are not. The features of many literary genres are intertwined in these narratives and the structures that does not belong to the folk tales draws attention. For example, in a single narrative, the characteristics of genres of popular literature such as fairy tales, myths and epics can be represented. Especially it is not to be overlooked as writer adds his own thoughts to the narrative in the parts that includes social phenomena. One of the noteworthy elements is that the place names in the tales are referred to the genuine-and-Turkish poets. There is another story in the narrative. In short, Vecihi Timuroğlu also used intertextuality.